Prepregnancy overweight and obesity are associated with impaired child neurodevelopment. Issue 1 (21st June 2017) - Widen, Elizabeth Marie; Kahn, Linda Gross; Cirillo, Piera; Cohn, Barbara; Kezios, Katrina Lynn; Factor‐Litvak, Pam
Abstract: The authors examined the relationship of prepregnancy body mass index (BMI) and gestational weight gain (GWG) with child neurodevelopment. Mother–child dyads were a subgroup ( n  = 2, 084) of the Child Health and Development Studies from the Oakland, California, area enrolled during pregnancy from 1959 to 1966 and followed at child age 9 years. Linear regression was used to examine associations between prepregnancy BMI, GWG, and standardized Peabody Picture Vocabulary Test and Raven Progressive Matrices scores and to evaluate effect modification of GWG by prepregnancy BMI. Before pregnancy, 77% of women were normal weight, 8% were underweight, 11% were overweight, and 3% were obese. Associations between GWG and child outcomes did not vary by prepregnancy BMI, suggesting no evidence for interaction. In multivariable models, compared to normal prepregnancy BMI, prepregnancy overweight and obesity were associated with lower Peabody scores (b: −1.29; 95% CI [−2.6, −0.04] and b: −2.7; 95% CI [−5.0, −0.32], respectively). GWG was not associated with child Peabody score [b: −0.03 (95% CI: −0.13, 0.07)]. Maternal BMI and GWG were not associated with child Raven score (all P  >0.05). Maternal prepregnancy overweight and obesity were associated with lower scores for verbal recognition in mid‐childhood. These results contribute to evidence linking maternal BMI with child neurodevelopment. Future research should examine the role of higher prepregnancy BMI values and the pattern of pregnancy weight gain in child cognitive outcomes.